ASSOCIATION OF NON-ALCOHOLIC FATTY LIVER DISEASE WITH SERUM URIC ACID - Abbasi, Sarwat; Haleem, Nadia; Jadoon, Sara; Farooq, Amjad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Non-alcoholic fatty liver disorder is a clinicopathological condition, characterized by macro vesicular steatosis in hepatic cells and metabolic stress related disorders without other causes of chronic hepatic disease. Uric acid is basically a heterocyclic compound of hydrogen, carbon, oxygen and nitrogen. Uric acid is the metabolic end product of purine metabolism. Hyperuricemia is considered to be related with the causes responsible for the production of metabolic syndrome. It may cause gout, impaired renal function, hypertension, hypertriglyceridemia, obesity and diabetes mellitus. The objective of study is to investigate the association of non-alcoholic fatty liver disease (NAFLD) and serum uric acid level. METHODS: This cross-sectional study was conducted at Ayub Teaching institute Abbottabad. According to predesigned questionnaire and informed consent, 100 subjects between ages 40-50 years were selected for the study. Data collected and analysis done by SPSS version 20. RESULTS: It was observed that 20(40%) subjects developed NAFLD as compared to 30(60%) of the subjects with normal serum uric acid level. Chi-square test was applied and values found to be significant (p=0.013). CONCLUSION: Our study shows association of NAFLD with serum uric acid level. Keywords: Non-alcoholic fatty liver disease; serum uric acid level; hepatic disorder